1995
DOI: 10.1038/bjc.1995.170
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and colon cancer incidence: a prospective cohort study

Abstract: al., 1984;Ferraroni et al., 1989;Bidoli et al., 1992) and cohort studies (Pukkala and Teppo, 1986;Vagero and Persson, 1986;Leon, 1988) showed predominantly positive associations between SES and colon cancer risk. In these studies hardly any adjustment was made for potential confounders. Most of the time, age was included in the analyses, and two studies included some lifestyle characteristics such as smoking (Williams and Horm, 1977) and coffee and alcohol consumption (Ferraroni et al., 1989 (Goldbohm et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…6 This was thought to be due to known risk factors for CRC, including lower occupational physical activity and dietary factors such as a higher intake of meat and eggs in the higher social class. 6 Similar results were found in a Dutch cohort-nested case-control study performed in 1995, 7 in which a positive association was found for cancer in the colon in the highest education levels. A large cohort study conducted in Finland reported higher standardized incidence ratios for cancer in both the colon and rectum in higher social classes.…”
supporting
confidence: 77%
“…6 This was thought to be due to known risk factors for CRC, including lower occupational physical activity and dietary factors such as a higher intake of meat and eggs in the higher social class. 6 Similar results were found in a Dutch cohort-nested case-control study performed in 1995, 7 in which a positive association was found for cancer in the colon in the highest education levels. A large cohort study conducted in Finland reported higher standardized incidence ratios for cancer in both the colon and rectum in higher social classes.…”
supporting
confidence: 77%
“…While education is a surrogate for socioeconomic status, which has been suggested to be associated with breast and colorectal cancer incidence rates [34,35], the positive association observed here might be partly due to greater cancer risk awareness in participants with a higher education level.…”
Section: Discussionmentioning
confidence: 66%
“…Only the significant association between social position and the risk of colon cancer persisted after further adjustment for other risk factors for colon cancer (P = 0.005), but the highest risk was found only in the highest social status (RR = 2.60, 95% CI 1.31 to 5.14). In women, there were no clear associations between indicators of socioeconomic status and colorectal cancer (25) . Italian study did combination of two hospital-based case-control studies conducted in six Italian centers between 1985 and 1996 found that, compared with individuals with less than 7 years of education, the odds ratio for colon (22) .…”
Section: Discussionmentioning
confidence: 79%